Integrated Nutrient Management for Sustainable Production of Cassava in Konkan Region - Mhaskar, N. V; Jadye, A. T; Haldankar, P. M; Chavan, S. A; Mahadkar, U. V (JOURNAL OF ROOT CROPS, 2014)
Integrated nutrient management (INM) is basically the complementary use of organic, inorganic and biological sources of plant nutrients to maintain and sustain soil fertility and enhance crop productivity. For standardization of INM package for cassava under Konkan region, field experiments were conducted at AICRP on Tuber Crops Centre at Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli during 2008 to 2011. The experiment was laid out in randomized block design with three replications. Cassava var. Sree Jaya was used for the study. The thirteen treatments comprised recommended dose of FYM + NPK and combinations of 3/4 the recommended dose of FYM + NK with vermicompost @ 200 kg ha-1, dhaincha @ 20 kg ha-1, Glyricidia green leaf manure @ 25 t ha-1 and cowpea @ 20 kg ha1 and FYM alone. All the above treatments were supplemented with panchagavya drenching @3% and without drenching of panchagavya. The pooled analysis revealed that significantly highest tuber yield of 45.67 t ha-1 was obtained in the treatment combination 3/4th recommended dose of FYM+ NK +Glyricidia green leaf manure @ 25 t ha-1 with drenching of panchagavya. Application of 3/4th recommended dose of FYM+ NK + dhaincha @ 20 kg ha-1 as green manure with drenching of panchagavya also yielded well (42.43 t ha-1) and gave highest net returns of ` 90, 462 ha-1 and B: C ratio of 1.88. Besides the major nutrient status of the soil was also improved due to this treatment.